Design and suggestions on open natural gas infrastructure system based on synergetic supply guarantee responsibilities - Wen WEN; Guojun HUANG; Chao WU; Yigong YIN; Rui YANG; Meng SUN (You-qi chuyun)
Objective The establishment of China Oil and Gas Pipeline Network Corporation signifies a significant milestone, indicating that the market-oriented reform of the natural gas industry in China has transitioned into a new phase. Despite the rising demand for natural gas in China, the industry is still in its nascent phase concerning infrastructure fairness and openness, and the supply guarantee of natural gas remains a significant challenge. Methods In the present research, the fairness and openness of natural gas infrastructure and supply guarantee were explored within a framework system. A thorough analysis was conducted to uncover the current status and existing issues concerning the infrastructure fairness and openness in China's natural gas market, to reveal the dual impacts of fairness and openness on supply guarantee, and to highlight the experience of natural gas market reforms in typical foreign countries. Based on the analysis results, this study introduced an open natural gas infrastructure system design with synergetic supply guarantee responsibilities. Additionally, conceptual pathways and policy suggestions were proposed for the development of infrastructure fairness and openness in conjunction with supply guarantee. Results The open natural gas infrastructure system featuring fairness and openness with synergetic supply guarantee responsibilities includes four key elements: supply guarantee, fairness and openness, the relationship between the first two elements, and the roles of pipeline operators. The demand for supply guarantee is classified into development demand and emergency demand, corresponding with different methods of supply guarantee. Crucial prerequisites for infrastructure fairness and openness involve infrastructure development, the segregation of transmission and sales operations, information disclosure, transparent procedures, rational pricing, and stringent regulation. Among the four elements, infrastructure fairness and openness play a role in promoting the supply guarantee of natural gas, and pipeline operators act as the subjects of fairness and opening responsibilities and the important contributors to the natural gas supply guarantee. It is recommended to delineate the scope and methods of supply guarantee, as well as the obligations and roles of market entities, to refine mechanisms related to fairness and openness, and to advance the construction of "One Pipeline Network". Conclusion The high-quality fairness and openness of infrastructure is beneficial for enhancing China's capacity to secure oil and gas supply.